2018
DOI: 10.1590/s1677-5538.ibju.2017.0339
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for prolonged hospital stay after retropubic radical prostatectomy in a high-volume teaching center

Abstract: Objective: To evaluate the length hospital stay and predictors of prolonged hospitalization after RRP performed in a high-surgical volume teaching institution, and analyze the rate of unplanned visits to the office, emergency care, hospital readmissions and perioperative complications rates. Materials and Methods: Retrospective analysis of prospectively collected data in a standardized database for patients with localized prostate cancer undergoing RRP in our institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 91%
“…Most previous studies of prolonged hospitalization have focused on specific sub-groups of patients such as orthopaedic procedures [ 21 , 24 , 26 , 29 , 30 , 31 , 39 ], cardiovascular disease [ 13 , 15 , 17 , 36 , 37 , 38 ], solid organ transplantation [ 33 , 50 ], or oncological conditions [ 11 , 14 , 18 , 20 , 27 , 28 , 34 , 35 ] ( Supplementary Table S7 ). A limited number of studies have examined the epidemiology of prolonged hospitalization in internal medicine patients [ 23 , 45 , 51 ] but only one of these was multi-centre in nature [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 In a NSQIP study on 864 patients undergoing radical nephrectomy, Lorentz et al 12 found that age, hematocrit level, heart failure, functional dependence, and open procedures were associated with longer recovery. As for patients undergoing prostatectomy, Coelho et al 16 showed that age, American Society of Anesthesiology score >3, large prostate, African American race, and prolonged operative times were the main predictors of pLOS. In addition, Charlson comorbidity index >2 was also associated with LOS > 1 day in patients undergoing RARP.…”
Section: Discussionmentioning
confidence: 99%
“…The category LOS = 2 days was created to account for delays due to logistics or conditions requiring medical observation, and the cutoff for pLOS was set at LOS > 2 based on previous studies and clinical experience. 16 , 17 Thus, we hypothesize that the predictors associated with pLOS are different than either LOS ⩽ 1 day or LOS = 2 days. All patients were categorized into one of the three groups, and only patients with missing LOS were excluded.…”
Section: Methodsmentioning
confidence: 99%